A identidade água abaixo: os reassentados da usina hidrelétrica Dona Francisca - RS - Marques, Maria Madalena dos Santos (2005)
This study implies an evaluation of the social identity of people who were resettled from their original place of living because a hydroelectric power plant was built (Dona Francisca). The objectives of the study were focused on revealing problems that emerged from this reallocation, for example degree of identification of families to the new place, organization of the people, people’s expectative, and so on. The methodology employed was case study which belongs to the qualitative paradigm. The case was the group “Por do Sol Tupa-I”. In particular, deep interviews were carried out within the group and recorded. After that, a qualitative analysis was performed following the objectives of the study. In addition, reviewing of documents and records was also utilized to support results. The results indicate that families are not satisfied with their general situation, including those that were resettled from the beginning. After four years they continue the process of adjustment to the new environment. The main problem that emerged was that the production system and the social relations that sustained their lives changed abruptly. The expectative of the people is to return to live to the old place or at least close to it.